Strategi Manajemen (POAC) Tradisi Maudu Lompoa Sebagai Event Pariwisata Di Desa Cikoang Kecamatan Mangarabombang Kabupaten Takalar - Anugrah Alam, Fachrian; Maulana Irsan, Dimas (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
Takalar is one of the regency in South Sulawesi Province which has diverse natural and cultural wealth. Maudu lompoa is one of the cultural traditions in Takalar regency which is held every year. The tradition is carried out to commemorate the birth of the Prophet Muhammad SAW. This research and writing aims to identify the management strategy (POAC) of the Maudu’ Lompoa tradition as a leading tourist attraction in Cikoang Village, Takalar regency. This research was conducted using direct observation, interviews, and literature studies. . The results of the study show that the application of management functions (planning, organizing, actuating, controlling) forms the basis of the strategy for developing the maudu lompoa tradition to become a leading attraction. Keywords: Maulid, Maudu’ Lompoa, POAC,  Tradition